G168 An observational study of clinician's gaze behaviour during simulated paediatric emergencies. (12th March 2018) - McNaughten, B; Hart, C; Gallagher, S; Junk, C; Coulter, P; Thompson, A; Bourke, TW
Abstract : Aims: Clinicians collect, prioritise and respond to visual cues when making decisions about patient care. This is of particular importance in the resuscitation environment where they are required to absorb and process large volumes of complex visual information in a time critical manner. Eye tracking technology allows for the measurement of an observer's point of gaze based on where their pupil is focused. Eye tracking technology has been used in aviation and surgery to describe differences in the gaze behaviour between experts and novices. The aim of this study was to describe the gaze behaviour of clinicians from different training backgrounds during a simulated paediatric emergency. Methods: Twenty-seven clinicians from different clinical areas within a tertiary children's hospital undertook a standardised, six minute, high fidelity simulated paediatric emergency. Participants wore SMI Eye Tracking Glasses. We measured the number of times participants looked at predefined key areas (fixation count) and the duration of time spent looking at each of these areas (dwell time). The time taken to key clinical interventions was also recorded. Results: Participants from all groups looked more frequently and for longer at the patient (chest and airway) than any of the other key areas of interests. Paediatric Intensive Care Unit (PICU) consultants focused longer on the chest and airway than any other groups. The gaze behaviour of paediatric consultants and trainees was similar. Both groups spent longer looking at the defibrillator and algorithm (51, 180 ms and 50, 551 ms respectively) than the PICU consultants and consultants in paediatric emergency medicine (19, 804 ms and 28, 095 ms respectively). The PICU consultants were quickest to perform key clinical interventions. Conclusions: This study is the first to describe differences in the gaze behaviour between clinicians from different backgrounds during a simulated paediatric emergency. Differences observed between experts and novices are similar to those described in aviation and surgery. Further research is needed to evaluate the potential use as an educational tool in the resuscitation setting.